044 Slow oscillatory transcranial direct current stimulation enhances cognitive performance during subsequent sleep deprivation. (3rd May 2021) - Hughes, John; Doty, Tracy Jill; Ratcliffe, Ruthie; Balkin, Thomas
Abstract: Introduction: The EEG slow oscillation of < 1 Hertz frequency has been implicated in various sleep functions, sparking a recent interest in slow oscillation enhancement strategies. In a seminal study, Marshall et al. (2006) demonstrated that 25 minutes of a slow oscillatory form of transcranial direct current stimulation (SO-tDCS) during early nocturnal sleep improved subsequent retention of word pairs learned prior to sleep, consistent with a proposed role for the slow oscillation in sleep-related memory consolidation. Another proposed function of the slow oscillation is synaptic downscaling, hypothesized to constitute the physiological basis for satisfying the homeostatic drive for sleep, per the synaptic homeostasis hypothesis of Tononi and Cirelli. We sought to determine if SO-tDCS could enhance the restorative properties of sleep, by enhancing slow oscillation activity, during a restricted sleep opportunity by assessing performance during a subsequent period of sleep deprivation (SD). Methods: Twenty-six healthy volunteers were randomized into two groups. Participants either received electrical stimulation with 50 minutes of SO-tDCS at 0.75Hz, or sham stimulation, during the second hour of a restricted two hour sleep opportunity (11:00PM TO 1:00AM), followed by a 46 hour period of SD and then two recovery nights of sleep. Vigilance was assessed periodically with the Psychomotor Vigilance Test (PVT) during a baseline day, SD, and during the two days following recovery sleep nights. Results: A mixed linear regression revealed significant main effects of day, group, and the interaction between group and day on mean reaction time (RT). Posthoc analysis revealed faster RTs following stimulation on day 2 of SD. It was also found that participants in the stimulation group had fewer major lapses (RTs > 500 ms) than those in the sham group over the first three days following stimulation. Conclusion: Slow oscillatory transcranial direct current stimulation during a portion of a restricted period of sleep appears to enhance sleep's restorative properties and improves cognitive performance during subsequent sustained wakefulness. The mechanistic basis for this phenomenon may be increased slow oscillation induced synaptic renormalization. Support (if any): Department of Defense Military Operational Medicine Research Program (MOMRP)